Effect of digital economy development on carbon emission intensity: evidence from Chinese provinces - Chen, Wen-Shuo; Jiang, Yu-Tong (Frontiers in Environmental Science, 2025)
IntroductionReducing carbon emission intensity is a crucial element in advancing sustainable development in China. In the context of continuous technological progress, the expansion of the digital economy may provide avenues for emissions reduction.MethodsThis paper constructs an index to measure digital economy progress using the entropy approach, based on data from 30 Chinese provinces from 2010 to 2024. Panel data regression models are then applied to examine the relationship between digitalization and carbon emission intensity, along with the mediating mechanisms involved.ResultsBaseline regression estimates suggest that both the overall digital economy index and its three core sub-components (with coefficients of −1.801, −7.784, −6.904, and −3.165, respectively) are associated with declines in carbon emission intensity, pointing to a potential mitigating effect. Considerable regional heterogeneity is observed, with the eastern and central regions exhibiting a more pronounced and statistically significant negative association, while the effect appears weaker and statistically insignificant in the western region.DiscussionFurther analysis of mediating pathways indicates that improvements in economic structure and innovation capacity may serve as channels through which digital economy development contributes—albeit to varying degrees—to reducing carbon emission intensity.